Optimizing Routes and Transportation Modes in Package Delivery Using the Saving Matrix Method - Hidayat, Agung Prayudha; Kartinawati, Annisa; Dardanella, Derry; Siskandar, Ridwan; Angeli, Jahira; Naoval Nainggolan, Zacky; Zaky Triyoga, Faishal (Jurnal Sains Indonesia, 2023)
Economic growth experienced a decline in the industrial sector, especially in transportation and warehousing. One way to improve distribution performance using transportation to determine the number of fleets used for delivery is by determining distribution routes that produce the shortest distance using the saving matrix method. The research results show that the optimization of the transportation mode is 2 vehicles with route savings of 27 Km for vehicle-1, and 23 Km for vehicle-2. This has an impact on Goods Delivery Service companies being able to optimize distribution costs from saving on the number of transportation modes that have been used so far from 4 vehicles to 2 vehicles.